Evaluation of a comprehensive non-toxic, biodegradable and sustainable cutting fluid developed from coconut oil. (September 2021) - Suvin, PS; Gupta, Poorva; Horng, Jeng-Haur; Kailas, Satish V
The evolution in development of cutting fluid from petroleum based products have brought about remarkable changes to the present and growing machining industry. Most of the cutting fluids are made of mineral base oils which are toxic, non-biodegradable and unsustainable. A major issue lies in their inappropriate disposal which results in surface water and groundwater contamination and consequently, agricultural products and food contamination. Hence, the objective of this study is to develop an alternative, sustainable, non- toxic and completely bio-degradable cutting fluid to replace the mineral oil based cutting fluid. A Green cutting fluid [GCF] was prepared by combining nontoxic emulsifiers and natural additives. GCF meets many of the characteristic specifications of commercial formulations with the added advantage that it is eco-friendly. Toxicity test for cutting fluids has been carried out using fish toxicity test (OECD -203). The GCF with green additives has an LC50 value ≥1064 mg/L. Commercial cutting fluid (CCF) has an LC50 value less than 100 mg/L These tests show that commercial cutting fluids are highly toxic, while the GCF can be considered as non-toxic. Biodegradability test was done using BOD-COD technique and found GCF as biodegradable and CCF as non-biodegradable. The ASTM D4627 corrosion tests infer that the GCF with grade 3 has better anticorrosive characteristics when compared to grade 4 of most CCF samples tested this could be possibly by the effect of natural additives in GCF. Drilling experiments were carried out to evaluate the machining performance of cutting fluids. Results from the drilling tests comparing the axial force/cutting force and torque showed that the performance of the GCF was comparable to that of the CCFs. Nevertheless, GCF formulation with non- toxic emulsifiers and natural additives is a good basis for further development and use of non-toxic tribological products.